(untitled) (Research, Society and Development, 2020)
Active Learning Methodologies aims to offer a learning approach that is different from traditional methods. These approaches seek to reconcile the changes that students undergo as a result of the evolution of society and, consequently, changes in the labor market. Problem Based Learning (PBL) presents itself as a form of active methodology that seeks to build student knowledge from the problem solving process. The study aims to apply the PBL in Geographic Information Systems (GIS) discipline of the Environmental Engineering course at Federal University of Triângulo Mineiro. The method was applied in two different classes, which were divided into smaller groups. In order to assess the dynamics of the PBL, anonymous questionnaires were applied to students after the method was finalized. The results showed that 88% of the students considered the PBL adequate to GIS. In addition, 94% of students were satisfied with the score distribution adopted and 70% of students assessed their own performance well. Therefore, the PBL proved to be an efficient methodology to complement the student’s learning in GIS. It is recommended that future studies be carried out, varying the time of application and the number of students per group, aiming continuous improvement.